2006
DOI: 10.1080/07420520601089521
|View full text |Cite
|
Sign up to set email alerts
|

Short Sleep Is Associated with Obesity among Truck Drivers

Abstract: Recent studies suggest that short-sleep duration is independently associated with obesity in the general population. The population of truck drivers is of particular interest, because they frequently work irregular shifts that in turn are associated with short-sleep duration. In addition, truck drivers have a high prevalence of sedentary habits, poor diet, and obesity. The present study aimed at verifying the association between sleep patterns and factors associated with obesity in this population. The study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
77
2
31

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 19 publications
8
77
2
31
Order By: Relevance
“…(3,5,7,17,18) In such studies, the prevalence of OSAS has been determined by subjective instruments (17,18) or by polysomnography. (3,5,7) The prevalence of OSAS in the present study was lower than that reported in other studies and yet higher than that observed for the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3,5,7,17,18) In such studies, the prevalence of OSAS has been determined by subjective instruments (17,18) or by polysomnography. (3,5,7) The prevalence of OSAS in the present study was lower than that reported in other studies and yet higher than that observed for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Among those 65 references, only the studies by Moreno et al were found to have used this instrument in truck drivers. (17,18) In those studies, 26.1% of the population was found to be at high risk of developing OSAS. (17) The relevance of studies of OSAS in truck drivers is related to the inability of such individuals to maintain a satisfactory level of concentration and the necessary psychomotor coordination to drive, (1) which increases the risk of accidents.…”
mentioning
confidence: 99%
“…the waist circumference analysis, which was also higher in comparison with ratios observed in the South of Brazil (16)(17) . Although abdominal obesity and obesity itself increase cardiovascular risks, increased waist circumference is associated with obstructive sleep apnea, which results in oxyhemoglobin desaturation episodes, provoking frequent awakening at night and, hence, sleepiness during the day (18)(19) . Studies have demonstrated a positive relation between the presence of obstructive sleep apnea and greater risks of traffic accidents (20)(21) .…”
Section: Resultsmentioning
confidence: 99%
“…Em relação à dinâmica de trabalho imposta aos motoristas comerciais, estudos revelaram as péssimas condições laborais que estes indivíduos enfrentam 7,8 . Caminhoneiros tipicamente têm horários de trabalho irregulares e devem freqüentemente inverter o ciclo vigília-sono, dormindo de dia e permanecendo acordado à noite, levando a privação parcial de sono cronicamente 7 .…”
Section: Aspectos Do Sono Em Condutores Profissionais De Veículos Pesunclassified
“…Caminhoneiros tipicamente têm horários de trabalho irregulares e devem freqüentemente inverter o ciclo vigília-sono, dormindo de dia e permanecendo acordado à noite, levando a privação parcial de sono cronicamente 7 . Esta situação predispõe a elevados níveis de estresse, ao uso de abusivo de drogas e medicamentos psicoestimulantes 8 , aos distúrbios alimentares 7 , ao sedentarismo 8 , ao desenvolvimento de doenças crônicas 7 .…”
Section: Aspectos Do Sono Em Condutores Profissionais De Veículos Pesunclassified